Flexible regression and smoothing : using GAMLSS in R /: using GAMLSS in R. (2017) - Stasinopoulos, Mikis D; Rigby, Robert A; Heller, Gillian Z; Voudouris, Vlasios; Bastiani, Fernanda de
No abstract available